Efficacy of lebrikizumab in adolescent patients with moderate-to-severe atopic dermatitis: 16-week results from three randomized phase 3 clinical trials - Adelaide A. Hebert; Carsten Flohr; H. Chih-ho Hong; Alan D. Irvine; Evangeline Pierce; Hany Elmaraghy; Sreekumar Pillai; Zach Dawson; Sherry Chen; Clara Armengol; Elaine Siegfried; Stephan Weidinger (Taylor & Francis Group, 2024)
AbstractBackground Lebrikizumab, a high-affinity monoclonal antibody targeting IL-13, previously demonstrated clinical efficacy in three randomized, double-blind, placebo-controlled Phase 3 trials that included adults and adolescents with moderate-to-severe atopic dermatitis (AD): ADvocate1, ADvocate2, and ADhere.Aim This subset analysis evaluated 16-week physician- and patient-reported outcomes of lebrikizumab in the adolescent patients enrolled in these three trials.Methods Eligible adolescents (≥12 to <18 years weighing ≥40kg) were randomized 2:1 to subcutaneous lebrikizumab (500 mg loading doses at baseline and Week 2 followed by 250 mg every 2 weeks) or placebo as monotherapy in ADvocate1&2, and in combination with topical corticosteroids (TCS) in the ADhere study. Week 16 analyses included clinical efficacy outcomes (IGA (0,1) with ≥2-point improvement, EASI 75, EASI 90), patient-reported Pruritus NRS ≥4-point improvement and Sleep-Loss Scale ≥2-point improvement.Results Pooled ADvocate1&2 16-week results in lebrikizumab (N = 67) vs placebo (N = 35) were: IGA (0,1) 46.6% vs 14.3% (p < 0.01), EASI 75 62.0% vs 17.3% (p < 0.001), EASI 90 40.7% vs 11.5% (p < 0.01), Pruritus NRS 48.9% vs 13.1% (p < 0.01), and Sleep-Loss Scale 26.9% vs 6.9% (p = 0.137). Corresponding results for ADhere, (lebrikizumab + TCS, N = 32; placebo + TCS, N = 14), were consistent.Conclusions Lebrikizumab treatment demonstrated efficacy in improving the signs and symptoms of AD in adolescent patients, consistent with the ADvocate and ADhere overall population results.